2022
DOI: 10.1186/s12885-022-09398-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of LAGE3 with unfavorable prognosis and promoting tumor development in HCC via PI3K/AKT/mTOR and Ras/RAF/MAPK pathways

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most common clinical malignancies quite susceptible to recurrence and metastasis. Despite several improvements in therapeutic approaches, the prognosis remains poor due to the limited treatment options. A bioinformatics analysis based on TCGA databases revealed that the recombinant human L antigen family member 3 (LAGE3) might function as an effective prognostic and diagnostic biomarker for HCC, as LAGE3, a protein-coding gene, maintains s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The study of Li et al. showed that LAGE3 has prognostic value in HCC, which may affect the progression path of HCC tumor by promoting the proliferation, survival, migration, invasion and anti-apoptosis of HCC cells through the PI3K/AKT/mTOR and Ras/RAF/MAPK pathways ( 53 ). Guo et al.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Li et al. showed that LAGE3 has prognostic value in HCC, which may affect the progression path of HCC tumor by promoting the proliferation, survival, migration, invasion and anti-apoptosis of HCC cells through the PI3K/AKT/mTOR and Ras/RAF/MAPK pathways ( 53 ). Guo et al.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the aggressive and unintentional spread of cancer is caused by erroneous phenotypes that result from DNA replication [61]. It is possible to effectively analyze the PI3K/AKT/mTOR signaling pathway as an appropriate treatment option because it is connected with several elements of cell growth and survival and is commonly activated in many different types of cancer [62]. The PI3K/AKT/mTOR axis can exhibit oncogenic activity by blocking autophagy and senescence processes while concurrently promoting cell growth, survival, migration, and invasiveness [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the aggressive and unintentional spread of cancer is caused by erroneous phenotypes that result from DNA replication (43). It is possible to effectively analyze the PI3K/AKT/mTOR signaling pathway as an appropriate treatment option because it is connected with several elements of cell growth and survival and is commonly activated in many different types of cancer (44). The PI3K/AKT/mTOR axis can exhibit oncogenic activity by blocking autophagy and senescence processes while concurrently promoting cell growth, survival, migration, and invasiveness (45,46).…”
Section: Discussionmentioning
confidence: 99%